Respon Morfo-fisiologi Empat Genotipe Cabai Rawit (Capsicum frutescens L.) terhadap Cekaman Salinitas - Baiq Arriyadul Badi'ah; Sobir; Syukur, Muhammad; Kusumo, Yudiwanti Wahyu Endro (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
The responses of cayenne pepper to salinity need to be elucidated for developing saline tolerant varieties. The study aimed to reveal the morphological and physiological responses of four cayenne pepper genotypes under salinity stress conditions. The research was conducted at the Tajur 2 experimental station of IPB University, Bogor, Indonesia, from October 2019 to March 2020. A two-factor randomized complete block design with five blocks as replications was used in this experiment. The first factor is the genotype of cayenne pepper (Sigantung, CR10, CSR1, and CRK1) and the second factor is salinity level (0-1, 2-4, 5-7, and 8-10 mS cm-1). The results indicated that the salinity significantly affected the morphological and physiological traits of cayenne pepper plants. Salinity 8-10 mS cm-1 on morphological traits caused the highest decrease in the number of flowers (74.65%), number of leaves (71.23%), fruit weight (58.48%), and root length (49.81%). In addition, a concentration of 8-10 mS cm-1 also caused the highest decrease in physiological traits. The highest effect of the treatment occurred in stomata conductance (29.37%), transpiration rate (26.47%), intercellular CO2 concentration (21.83%), and chlorophyll index (20.19%). Based on the average value of the stress sensitivity index (ISC), the Sigantung (1.2) and CSR1 (1.0) genotypes were categorized as salinity sensitive (ISC >1.0). On the other hand, CR10 and CRK1 had an average ISC value of 0.8, so they were categorized as the moderate tolerance to salinity (0.5<ISC<0.1). Keywords: stomatal conductance, intercellular CO2 concentration, stress sensitivity index, root length